1993
DOI: 10.1128/jb.175.13.4016-4024.1993
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory interactions between RepA, an essential replication protein, and the DNA repeats of RepFIB from plasmid P307

Abstract: The control of RepFIB replication appears to rely on the interaction between an initiator protein (RepA) and two sets of DNA repeat elements located on either side of the repA gene (BCDD'D" and EFGHIJ). In vivo genetic tests demonstrate that the BCDD'D" repeats form part of the origin of replication, while some of the downstream repeat elements (HIJ) are involved in the sensing and setting of plasmid copy number. RepA DNA binding to these groups of repeats has been investigated in vivo by utilizing the fact th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Replication group 1 contained domains for rolling circle initiator proteins (Rep_1 [ 41 ], Rep_2 [ 42 , 43 ], RepL [ 44 , 45 ], and the excluded Rep_trans [ 46 ]), while groups 2 and 3 contained domains of theta replication initiators (Rep_3 [ 47 , 48 ] and Replicase [ 49 ]). Therefore, it makes sense that the group 1 replication domains are the ones that are the most entangled with bacteriophages, which also use rolling circle replication ( 50 ).…”
Section: Resultsmentioning
confidence: 99%
“…Replication group 1 contained domains for rolling circle initiator proteins (Rep_1 [ 41 ], Rep_2 [ 42 , 43 ], RepL [ 44 , 45 ], and the excluded Rep_trans [ 46 ]), while groups 2 and 3 contained domains of theta replication initiators (Rep_3 [ 47 , 48 ] and Replicase [ 49 ]). Therefore, it makes sense that the group 1 replication domains are the ones that are the most entangled with bacteriophages, which also use rolling circle replication ( 50 ).…”
Section: Resultsmentioning
confidence: 99%
“…Replication group 1 contained domains for rolling circle initiator proteins (Rep_1 55 , Rep_2 56,57 , RepL 58,59 , and the exluded Rep_trans 60 ), while groups 2 and 3 contain domains of theta replication initiators (Rep_3 61,62 and Replicase 63 ). It therefore makes sense that group 1 replication domains are the ones that are the most entangled with bacteriophages, which also use rolling circle replication 8 .…”
Section: Resultsmentioning
confidence: 99%
“…In several other replicons related to RepHI1B, the operator/promoter of the gene coding for the initiator protein has likewise been located in the origin of replication. These include P1 (Chattoraj et al 1985), RepFIB (Spiers et al 1993), Rts1 (Itoh et al 1987), and RepHI1A (Newnham and Taylor 1994). In the case of P1, it has been shown that it is the monomeric form of RepA that binds all the repeats (Wickner et al 1991).…”
Section: Discussionmentioning
confidence: 99%